Triggering Receptor Expressed on Myeloid cells-1: a new player in platelet aggregation - Jolly, Lucie; Lemarié, Jérémie; Carrasco, Kevin; Popovic, Batric; Derive, Marc; Boufenzer, Amir; Gibot, Sébastien (Thrombosis and Haemostasis, 2017)
Triggering Receptor Expressed on Myeloid cells-1 (TREM-1) is an immunoreceptor initially known to be expressed on neutrophils and monocytes/macrophages. TREM-1 acts as an amplifier of the inflammatory response during both infectious and aseptic inflammatory diseases. Another member of the TREM family, The Triggering receptor expressed on myeloid cells Like Transcript-1 (TLT-1) is exclusively expressed in platelets and promotes platelet aggregation. As the gene that encodes for TLT-1 is located in the TREM-1 gene cluster, this prompted us to investigate the expression of TREM-1 on platelets. Here we show that TREM-1 is constitutively expressed in α-granules and mobilised at the membrane upon platelet activation. Pharmacologic inhibition of TREM-1 reduces platelet activation as well as platelet aggregation induced by collagen, ADP, and thrombin in human platelets. Aggregation is similarly impaired in platelets from Trem-1−/− mice. In vivo, TREM-1 inhibition decreases thrombus formation in a carotid artery model of thrombosis and protects mice during pulmonary embolism without excessive bleeding. These findings suggest that TREM-1 inhibition could be useful adducts in antiplatelet therapies.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Platelets; TREM-1